1997
DOI: 10.1523/jneurosci.17-19-07523.1997
|View full text |Cite
|
Sign up to set email alerts
|

The Glutamate Receptor Subunit δ1 Is Highly Expressed in Hair Cells of the Auditory and Vestibular Systems

Abstract: In the inner ear, fast excitatory synaptic transmission is mediated by ionotropic glutamate receptors, including AMPA, kainate, and NMDA receptors. The recently identified ␦1 and ␦2 glutamate receptors share low homology with the other three types, and no clear response or ligand binding has been obtained from cells transfected with ␦ alone or in combination with other ionotropic receptors. Studies of mice lacking expression of ␦2 show that this subunit plays a crucial role in plasticity of cerebellar glutamat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
35
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 75 publications
5
35
0
Order By: Relevance
“…1F). Together, our results strongly suggest that Tlx3 is expressed only in differentiating VCG neurons, most of which are believed to use glutamate as a neurotransmitter (8). These results are consistent with those of previous studies in which Tlx3 was shown to be expressed only in postmitotic neurons, but not in multipotent neural progenitors (9, 10).…”
Section: Tlx3 Expression Is Confined To Postmitotic Neurons In Craniasupporting
confidence: 93%
“…1F). Together, our results strongly suggest that Tlx3 is expressed only in differentiating VCG neurons, most of which are believed to use glutamate as a neurotransmitter (8). These results are consistent with those of previous studies in which Tlx3 was shown to be expressed only in postmitotic neurons, but not in multipotent neural progenitors (9, 10).…”
Section: Tlx3 Expression Is Confined To Postmitotic Neurons In Craniasupporting
confidence: 93%
“…27 In line with this, mice lacking Grid1 showed impaired hearing. 28 In addition, Grid1 mRNA was detected in ganglion and bipolar retinal cells, 29 reminiscent of the Grid2 immunostaining profile.…”
Section: Discussionmentioning
confidence: 68%
“…Immunofluorescence was carried out as described (Safieddine et al, 1997) on cochleae from three deaf5/deaf5 mutants and two +/deaf5 littermate controls at postnatal day 6 (P6). Inner ear tissues were fixed overnight at 4°C in 4% paraformaldehyde in PBS followed by sinking in 25% sucrose.…”
Section: Immunofluorescence and Phalloidin Staining Of Hair Cellsmentioning
confidence: 99%